Does Brain-Based Learning Improve Mathematical Reflective Thinking Ability in Quadratic Functions?: A Quasi-Experimental Study - Michaelia, Nabila; Muntazhimah , Muntazhimah (Jurnal Paedagogy, 2025)
This research examined the impact of Brain-Based Learning model versus conventional model on mathematical reflective thinking abilities among State Senior High Schools students in Jakarta. Employing a quantitative quasi-experimental approach with nonequivalent control group design, the study involved 48 students selected from a population of 286 grade X students using purposive sampling. Data was collected through a three-essay assessment instrument based on mathematical reflective thinking indicators, previously validated for validity and reliability. Analysis included descriptive statistics, normality test, homogeneity test, and t-test. Results show that the experimental class achieved a higher average post-test score of 17.54 compared to the control class score of 9.37. The t-test revealed a significant difference with Sig (2-tailed) = 0.000 < 0.05, leading to the rejection of H0 and the acceptance of H1. Therefore, the Brain-Based Learning model significantly enhances students' mathematical reflective thinking skills compared to the conventional model. This finding confirms that brain-based learning is able to optimize students' cognitive processes in developing mathematical reflective thinking skills, which include aspects of reacting, comparing, and contemplating. The improvement of this ability is very important considering the low level of students' mathematical reflective thinking ability previously described in this research.